A curva de regressão da gonadotrofina coriônica humana é útil no diagnóstico precoce da neoplasia trofoblástica gestacional pós-molar? - Delmanto, Lúcia Regina Marques Gomes [UNESP]; Maestá, Izildinha [UNESP]; Neto, Antônio Rodrigues Braga; Michelin, Odair Carlito [UNESP]; Passos, José Raimundo De Souza [UNESP]; Gaiotto, Fernanda Régnier [UNESP]; Rudge, Marilza Vieira Cunha [UNESP] (My University, 2007)
PURPOSE: to evaluate the usefulness of the normal human chorionic gonadotropin (hCG) regression curve in the early diagnosis of post-molar trophoblastic neoplasia (GTN). METHODS: a longitudinal study including 105 patients with complete hydatidiform mole (CHM) followed up at the Botucatu Center of Trophoblastic Diseases from 1998 to 2005. Serial serum hCG titers were measured fortnightly in all patients. Individual curves of the 105 patients were built. Comparison between the normal regression curve established at our center with individual hCG curves was used to screen and diagnose (plateau/rise) GTN. The number of weeks postevacuation when hCG levels exceeded the normal limits was compared with the number of weeks when hCG reached plateau/rise. RESULTS: among the 105 patients with CHM, 80 reached spontaneous remission (SR) and 25 developed GTN. Among the 80 SR patients, 7 (8.7%) initially showed hCG concentrations above normal but eventually achieved remission. All the 25 GTN patients showed deviation from the normal hCG curve at 3.84±2.57 weeks and reached plateau or rise at 8.40±2.94 weeks (p<0.001). CONCLUSIONS: the normal regression curve of post-molar hCG is useful in the early diagnosis of GTN.
Are curves of human chorionic gonadotropin useful in the early diagnosis of post-molar trophoblastic neoplasia?
Keywords: Chorionic gonadotropin/diagnostic use; Hydatidiform mole; Trophoblastic neoplasms/diagnosis